Hubungan Religiuslitas terhadap Overthingking Ibu Rumah Tangga Di Perkumpulan Keluarga Berencana Indonesia (PKBI) - Fitri, Hartika Utami; Risti, Amelia; Suryati, Suryati; Rasmanah, Manah (Jurnal Consulenza : Jurnal Bimbingan Konseling dan Psikologi, 2023)
This research aims to determine the level of Overthinking  of Housewives in the PKBI Program. Second, to find out the relationship between the level of religiosity and Overthinking  of housewives in the PKBI program in Palembang City. This research uses a correlational quantitative descriptive approach with the product-moment correlation method, with a population of 22. Data collection techniques use questionnaires, observation and human docking. The instruments used were questionnaires developed from aspects of religiosity and Overthinking , data analysis techniques using validity, reliability, simple linear, and correlation (r) assisted by SPSS version.23. The results of the research show firstly, the level of Overthinking  for housewives in the PKBI program in Palembang City is in the medium category, with details namely that there are 8 people in moderate condition (86%), Overcoming Overthinking  for housewives with a more open condition and placing themselves in an environment with a high level of religiosity to balance thoughts that cause anxiety to become calm, especially for housewives who often overthink their children and husband. Second, the correlation between the level of religiosity and Overthinking  in housewives was obtained (p = 0.000 < 0.05), so it can be interpreted that there is a relationship between the level of religiosity and Overthinking  in housewives. in the Palembang City PKBI program Keywords: Overthingking;Religiocity. Homemaker